Reference point and case a cognitive grammar exploration of Korean - Park, Chongwon (Human cognitive processing ;, 2019)
"This monograph answers the rarely discussed questions of why complicated grammatical case phenomena exist in Korean and what the connection is between the case forms and their functions. The author argues that the case forms in Korean reflect patterns of the human cognitive process. While this approach may seem rather obvious to non-linguists, it is indeed a novel claim in contemporary linguistic theory. In order to provide technical analyses of Korean case phenomena such as multiple nominative/accusative, non-nominative subject, and adverbial case constructions, this book adopts an independently established descriptive construct known as reference point in the framework of Cognitive Grammar. The author demonstrates that if we adopt the notion of reference point, we not only explain a substantially wider set of data, but we also reach a more reasonable generalization. The intended audience of this book are researchers who are interested in case phenomena, without respect to their theoretical persuasions"--